The complete mitochondrial genome of Leptobotia taeniaps (Cypriniformes: Cobitidae). (3rd May 2016) - Wei, Min; Yu, Peng; Yang, Yingming; Wan, Quan
Abstract: Leptobotia taeniaps is a small-sized benthopelagic fish species in the famally Cobitidae. In the present study, the complete mitochondrial genome of L. taeniaps was determined. The complete mitochondrial genome of L. taeniaps was 16, 592 bp in length, containing 2 rRNA genes, 22 tRNA genes, 13 protein-coding genes, a control region, and an L-strand replication origin (OL ). Its overall nucleotide base composition of mitogenome was 31.08% for A, 15.95% for G, 24.98% for T and 27.99% for C, as well as an AT content of 56.06%.